Sistemas de membranas, nitrogênio equitosana na micropropagação e análise química de voláteis de Mentha arvensis e Mentha viridis - Oliveira, Thainá de (2017)
Among the medicinal plants, the genus Mentha, is one of the most used mainly because of the composition of essential oils, rich in monoterpenes, applicable to the pharmaceutical, cosmetic, food and perfume industries. The present study aimed to evaluate the effect of different nitrogen sources, alternative membrane systems and different doses of chitosan, on the growth, production of photosynthetic pigments and analysis of the volatile fraction of micropropagated species. Six experiments were set up, three with Mentha arvensis and three with M. viridis. In the nitrogen sources experiment, a nodal segment of approximately 1 cm per tube was inoculated into 15 mL of semi solid MS medium with 6 g / L of agar. Rates of NO3 and NH4 were T1 1/1; T2 1.4 / 1; T3 2/1; T4 3/1; T5 5/1, T6 11/1 and T7 only NO3. In the experiment of natural ventilation systems, a 3 x 4 factorial scheme was done, varying 3 doses of sucrose (0%, 1,5%, 3,0%) and 4 alternative systems of membranes WM (Without Membrane), ASM1 (Alternative System of Membrane One), ASM2 (Alternative System of Membrane Two), ASM4 (Alternative System of Membrane Four). The containers used for inoculation were flasks containing 45 mL of MS medium, with three explants per vial. And the chitosan experiments were inoculated 1 nodal segment of approximately 1 cm per tube in 15 mL of MS medium. It consisted of 5 different doses of elicitor, 0 mg / L, 50mg / L, 100mg / L, 150mg / L and 200mg / L. All were cultivated for 30 days in a growth room with photoperiod of 16h light. In the first experiment, when the source supplied was only NO3, they did not develop well and it was necessary to add NH4 to the medium. In Mentha arvensis, the 1.4 / 1 treatment produced higher pigment values for chlorophyll a, b and total chlorophyll. The treatment with only NO3 quantified larger pigments of chlorophyll b and total chlorophyll, and carotenoids. From the 3/1 treatment, there was an increasing linear trend of menthol and decreasing pulegone. In Mentha viridis, treatment with only NO3 provided more pigments for chlorophyll a and total chlorophyl, chlorophyll b had better response at the 11/1 rate, and carotenoids at 1/1. In the same species, there was a marked fall of carvone and increase of linalool and sabinene hydrate with the rate 11/1. In the second, it can be observed that the use of porous membranes together with the decrease of the sucrose in the in vitro culture, provided a better growth of the seedlings. Mentha arvensis produced higher values of chlorophyll a, b, total chlorophyll, and carotenoid pigments with 4 membranes and 3.0% sucrose. Mentha viridis obtained higher values for these pigments with 4 membranes and 1.5% of sucrose. The system with 4 membranes and sucrose was the one that provided greater area of menthol in Mentha arvensis. And the system with 1 membrane and 3.0% sucrose stimulated the largest production of linalool in Mentha viridis. And at last, in both species, the addition of chitosan influenced analysis of the volatile fraction and seedling growth. Chitosan affected the growth of M. arvensis and M. virids, being more pronounced in M. arvensis. The production of photosynthetic pigments responded better in treatments that did not contain chitosan. The elicitor affected the concentration of constituents in vitro. In the lower concentration of chitosan there was a greater accumulation of pulegone and less menthol. However, higher concentration occurred the inverse.